Bibliometric Computational Mapping Analysis of Publications on Financial Technology in Islamic Capital Market - Ahmad Fadlur Rahman Bayuny; Yana Rohmana (Review of Islamic Economics and Finance, 2022)
Purpose – This study aims to explore and categorize research literature on Financial Technology in Islamic Capital Market systematically by mapping and visualizing it through bibliometric analysis using VOSviewer. Methodology - The research from publications that have appeared in journals that are indexed by Google Scholar served as the foundation for the article data used in this study. A reference manager tool called Publish or Perish is used to gather research data. A literature review on the subject we chose was done with the help of the program Publish or Perish. Findings - The results show that research on Financial Technology in Islamic Capital Market is separated into 3 terms: Financial Technology, Islamic, Capital Market. The term "Financial Technology" is associated with 168 links with a total link strength of 581. The term "Islamic" has 191 links with a total link strength of 661. The term "Capital Market" has 219 links with a total link strength of 840. While the popular Islamic capital market research was carried out in 2019, namely 134 studies. Novelty – There have been many studies on bibliometric analysis, including bibliometric analysis in the field of economics, bibliometric analysis in Islamic economic research. However, research on financial technology and Islamic capital markets bibliometric analysis of published data specifically to determine research development has not been carried out. Research Limitation This study focuses on the financial technology in Islamic Capital Market in the last 10 years due to time constraint. Research Implication- The study presents how many articles have been published on financial technology in Islamic capital market and its relation to problem areas using VOSviewer.This review can be a basis for further research.